Giant sacrococcygeal teratoma embolization - Umberto G Rossi; Maurizio Cariati; Paolo Tomà (Indian Journal of Radiology and Imaging, 2013)
Resection of giant sacrococcygeal teratoma with high-vasculature in newborns can be a fatal procedure due to massive bleeding of the tumor. Endovascular embolization of the arteries that supply the tumor may lead to minimal blood loss. We present a case of giant high-vascular sacrococcygeal teratoma type-1 that was embolized in an infant born at 35 weeks gestation. This procedure lead to a safe, surgical resection with minimal bleeding: 12 ml.